Frequency of Hepatotoxicity Caused by ATT in Pulmonary Tuberculosis (Medical Forum Monthly, 2024)
Introduction: Tuberculosis is common disease caused by Mycobacterium Tuberculosis. Tuberculosis is one of the world's most widespread and deadly illnesses and infects an estimated 20–43% of the world's population and kills about 3 million people each year in the world. The common side effect of antituberculous drugs is hepatotoxicity. This study was carried out to determine the magnitude of hepatotoxicity caused by antituberculous drugs in patients of pulmonary tuberculosis.Objective: To determine the frequency of hepatotoxicity caused by ATT in pulmonary tuberculosis.Outcome measure: Frequency of hepatotoxicityStudy design: Cross sectional studyPlace and Duration of Study: This study was carried out in collaboration of Department of Medicine and Department of Pulmonology, Chandka Medical College, Civil Hospital Larkana from November 2010 to May 2011.Subjects: All consecutive sputum smears or culture positive patients or radiological evidence of active pulmonary T.B of either sex, older than 15 years of age were included in the study.Materials and Methods: After approval of ethical committee for medical research of Shaheed Mohtarma Benazir Bhutto University Larkana, informed written consent was taken from newly diagnosed patients of pulmonary tuberculosis for participation in the study. Blood samples were taken, coded and sent for determination of liver function test. Final outcome was measured at the end of 4th week. The data was analyzed using SPSS version 17.Results: A total of 256 patients were enrolled in this study during study period. The mean age of enrolled participants is 41.5±18.1. Of 256 patients, 132 (51.6%) were male and 124 (48.4%) were female. The male to female ratio was 1.06:1. Mean serum bilirubin was 1.5±0.7 mg/dl (Range 1.1-3.9mg/dl), the mean alanine transferase level was 34.7±11 IU/L (Range 11- 109 IU/L), aspartate transferase level was 35.4±19.3 IU/L (Range 11-112 IU/L) and alkaline phosphatase level was 150±38 IU/L (Range 95-280 IU/L).The frequency of hepatotoxicity was 51 (19.9%). Hepatotoxicity was observed in 25-35 age group was 21.7% and 56-65 years was 26%. Hepatotoxicity was observed in 23.4% female and 16.7% male.Conclusion: It is concluded from this study that patients taking anti tuberculosis therapy are vulnerable to hepatotoxicity. Screening should be done after starting of ATT in order to avoid liver damage.